Tapered optical fibre sensors employing nanostructured coatings - Jarzebinska, Renata (Cranfield University, 2010)
Tapered optical fibres have been manufactured, characterised and studied. These are compact devices made from single-mode optical fibre. A system for producing tapers has been developed, employing flame heating of the optical fibre and computer controlled rotation stages to stretch the fibre in a controlled and repeatable fashion. Subsequently tapered fibres were coated with nanostructured films of materials that change their optical properties in response to an external stimulus. An investigation of the effect of depositing chemically sensitive nano-scale films onto tapered optical fibres has been undertaken. Three different methods of deposition were applied: Langmuir-Blodgett technique, electrostatic-self-assembly and – for the first time - chemical grafting. Six different films of materials were deposited onto tapered fibres: 4-[2-(4-dimethylamino- naphtalen-1-yl)-vinyl]-1-octadecyl-quinolinium iodide (merocyanine dye), calix[4]resorcinarene, bilayers of poly(allyamine hydrochloride) (PAH) and anionic tetrakis(4-sulfophenyl)porphine (TSPP), PAH and cyclodextrine, TiO2 nanoparticles imprinted with ((1-(4-Nitrophenylazo)-2-naphthol (NPAN) compound), polyaniline (PANI). During the deposition process the light was launched into each fibre and the evolution of the transmission spectrum observed. The coated tapers were subsequently investigated for their potential application as chemical sensors: pH, red-ox, ammonia sensors. The response to a stimulus was investigated by immersing the coated tapered fibre in an environment containing the measurand. The properties of these devices were also used in combination other photonics concepts, such as fibre Bragg gratings written in the tapered region of a fiber, under investigation within the Engineering Photonics Group to develop new sensor elements.